INITIAL APPLICATION OF NONLINEAR REGRESSION MODELS TO ASSESS BIOLOGICAL SELF-PURIFICATION CAPACITY IN VUNG RO BAY (PHU YEN) - Huan, Nguyen Huu; Hieu, Nguyen Trinh Duc (Vietnam Journal of Marine Science and Technology, 2019)
The self-purification of waters is a complex process, including physical, biological and chemical processes. Based on experimental data in May 2014 and December 2014 in Vung Ro bay (Phu Yen), this paper assesses biological self-purification capicity through the biodegradation of organic matter and nutrient assimilation. The capacity of biodegradation of organic matter is represented by nonlinear regression models of the relationship between BOD and decay time: model of Streeter - Phelps, Young and Clark (1965); Mason et al., (2006). The capacity of nutrient assimilation is represented by the nonlinear regression models of the relationship between photosynthesis and irradiance: Model of Webb et al., (1974); Platt et al., (1980); Eilers and Peeters (1988). Using the least squares method on the nonlinear regression model, the parameters characterizing the self purification process in Vung Ro waters were identified. The study results indicated that the rate of organic biodegradation in Vung Ro waters was 0.1073 ± 0.0781 days-1 (with RMSE = 0.0663 ± 0.0386); the half-time of decay was about 6 days. The maximum intensity of photosynthesis in Vung Ro waters was 57.6881 ± 25.2211 mgC (mgChal)-1h-1 (with RMSE = 3.5900 ± 2.2170); maximum nutrient assimilation of phytoplankton was 9.1719 ± 3.5962 mgN/m3/h and 1.2693 ± 0.4977 mgP/m3/h